Effectiveness of Whatsapp-based Digital Education in Improving Knowledge and Early Detection of Preeclampsia in Pregnant Women - Darwati, Lilik; Muthoharoh, Husnul; Nikmah, Khusnul; Wasiah, Asyaul; Ningsih, Eka Sarofah; Darmawan, Erica Valenskie (Universitas Muhammadiyah Sidoarjo, 2026)
Preeclampsia is a pregnancy complication characterized by increased blood pressure and proteinuria after 20 weeks of gestation. This condition remains a leading cause of maternal and infant morbidity and mortality worldwide, including in Indonesia. This study aims to evaluate the effectiveness of education in improving pregnant women's knowledge about preeclampsia. The study used a quasi-experimental design with a pretest-posttest control group. This design was used to identify pregnant women by comparing the intervention and control groups before and after education. The study population was pregnant women undergoing prenatal care at the Kustini Turi Lamongan Health Center (TPMB) and meeting the inclusion and exclusion criteria. A sample of 30 respondents was drawn using a purposive sampling technique. The chi-square statistical test showed a p-value of 0.012 (p < 0.05), indicating a significant relationship between WhatsApp-based digital education and pregnant women's knowledge about preeclampsia. This suggests that pregnant women exposed to WhatsApp education tended to have better knowledge than those not exposed. Education through WhatsApp in this study contributed to increasing pregnant women's awareness of the importance of routine prenatal checkups and their awareness of pregnancy complications. With increased knowledge, it is hoped that the risk of undetected preeclampsia can be minimized. Pregnant women are expected to be more active in seeking health information and raising awareness of the importance of early preeclampsia detection. For further research, it is recommended to conduct studies with larger sample sizes and use more robust research designs to obtain more comprehensive results.